Live more: live better. Psychosocial strategy for comprehensive care of the elderly - Ortiz Quevedo, Jenny Patricia; Núñez Uribe, Ruth Johanna; Rosales, Andrea Navarrete; Sánchez Riaño , Federico (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Based on the multiple changes caused in current societies, in terms of the increase in life expectancy of human beings, this research addressed a study of psychosocial strategies that can prevent cognitive deterioration and improve the quality of life in people. old people. The research was developed, in a first phase, under a qualitative, descriptive approach, based on Norka Arellano's methodology and her reflexive critical action research design, through documentary analysis. In this article, the articulating axes of key multidimensional elements are presented with the main objective of proposing a psychosocial intervention strategy that allows promoting self-care - and that of the other in an integral process and that they can have a relationship and incidence of the social environment and family in the emotional state of the elderly.